The Complaint management Complaints of the Damrongtham Center Province Maha Sarakham - เลาหพันธ์, สรัล (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2021)
The objective of the research article were 1) to study the process of grievance management of the Damrongtham Center, Maha Sarakham Province, 2) to study the complaints management problem of the Damrongtham Center, Maha Sarakham Province, 3) to study the guidelines for the complaint management development of the Damrongtham Center, Maha Sarakham Province, It is a qualitative research. The sample used in the research consisted of 22 people. The instrument used in the research was interview form. Data were analyzed by descriptive analysis. The research found that: 1. The complaint management process of the Damrongtham Center, Maha Sarakham Province. The staff will explain and process the process for the petitioner. Know that after the petitioner has made a complaint will there be a step, how will the process go in which direction and how long will it take. In order to understand initially between the Damrongtham Center, Maha Sarakham Province and the complainant by conducting public complaints/grievances. 2. The problems in handling complaints/grievances of Damrongtham Center, Maha Sarakham Province. It can be seen that the process for grievance and grievances is complex and complex. 3. Guidelines for the Management of Complaints/Grievances of the Damrongtham Center, Maha Sarakham Province, a case study Damrongtham Mahasarakham Center. The research results were found that Damrongtham Center, Maha Sarakham Province. The method should be adjusted. Adjusting the system to receive complaints/grievances making a complaint in person complainants must bring their identity card with them every time they make a complaint or contact to inquire about the progress of the process of making a complaint the complaint system should be implemented electronically rather than written on paper. It is recorded in the computer system. Has a smart card system, or to educate the general public about the things that need to be prepared or need to be obtained in order to obtain information from the service, for convenience and speed in service And meet the purpose of requesting services public relations, or give knowledge Roles and responsibilities of service work, and classify actionable matters and matters that cannot be carried out with publicity through various channels.